2003
DOI: 10.1210/en.2002-220705
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Is Differentially Regulated in the Epididymis after Orchidectomy

Abstract: The epididymis is the site for the transport, maturation, and storage of spermatozoa. Regulation of epididymal structure and function is highly dependent on the ipsilateral testis. At the molecular level, however, few studies have been undertaken to determine which genes are expressed in the epididymis under testicular regulation. The goal of this study was to identify genes for which expression is regulated after orchidectomy, both throughout the epididymis and in a segment-specific manner. Microarrays spotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 297 publications
3
45
0
1
Order By: Relevance
“…33 The expression of defensins was not affected by castration in the corpus region, while caudal expression of defensins DEFB118-DEFB123 was not maintained at normal levels by exogenous testosterone, suggesting the requirement for additional testis factors as suggested previously. 25 Principal cells are particularly sensitive to circulating androgens and the androgen regulation of beta defensins may be cell and tissue specific.…”
Section: Discussionmentioning
confidence: 51%
“…33 The expression of defensins was not affected by castration in the corpus region, while caudal expression of defensins DEFB118-DEFB123 was not maintained at normal levels by exogenous testosterone, suggesting the requirement for additional testis factors as suggested previously. 25 Principal cells are particularly sensitive to circulating androgens and the androgen regulation of beta defensins may be cell and tissue specific.…”
Section: Discussionmentioning
confidence: 51%
“…In fact, the control of gene transcription by androgens varies along the epididymis and is differentially affected with progression of surgical castration (65). Microarray analysis of 474 genes was used to evaluate gene expression changes over the first seven days postsurgical castration in the initial segment, caput, corpus, and cauda epididymis from adult rats.…”
Section: Adult Testis and Epididymismentioning
confidence: 99%
“…Microarray analysis of 474 genes was used to evaluate gene expression changes over the first seven days postsurgical castration in the initial segment, caput, corpus, and cauda epididymis from adult rats. Several genes encoding proteins involved in cell viability and metabolism, as well as sperm maturation, were shown to be androgen-regulated (65). Microarray analysis of 31,000 genes indicated that, of the 1,059 genes that were affected by surgical castration after seven days, DHT treatment for seven consecutive days was capable of restoring over 75% of the gene levels toward the control, indicating that testosterone and DHT may differentially regulate the relative levels of such gene transcripts along rat epididymis (58).…”
Section: Adult Testis and Epididymismentioning
confidence: 99%
“…Importantly, distinctive region-specific epididymal gene expression changes also occur during aging and in response to other experimental manipulations, such as orchidectomy, caloric restriction, and vitamin E treatments (Jervis & Robaire 2002, Ezer & Robaire 2003. These responses clearly demonstrate the differential regulation of this tissue, however, surprisingly, little is known about how this regulation is achieved.…”
Section: Introductionmentioning
confidence: 99%